A Novel Signature of Necroptosis-Associated Genes as a Potential Prognostic Tool for Head and Neck Squamous Cell Carcinoma - Huang, Jing; Huo, Hongqi; Lu, Rong (Frontiers in Genetics, 2022)
Background: Head and neck squamous cell carcinoma (HNSCC) arises from squamous cells in the oral cavity, pharynx and larynx. Prognosis of HNSCC is poor. Necroptosis is a novel programmed form of necrotic cell death. The prognostic value of necroptosis-associated gene expression in HNSCC had not been explored. Material and Methods: We downloaded mRNA expression data of HNSCC patients from TCGA databases and Gene Expression Omnibus (GEO) databases. Gene expression between tumor tissues and adjacent normal tissues was compared to identify differentially expressed genes (DEGs). Necroptosis-related prognostic genes were then identified by univariate Cox regression. LASSO was used to establish a model with necroptosis-related genes. Kaplan-Meier analysis and ROC were applied to verify the model.A data set (GSE65858, n = 270) from GEO was used to verify the model's predictive ability. Finally, gene set enrichment analyses, immune microenvironment analysis, principal component analysis, and anti-tumor compound IC50 prediction was performed. Results: We identified 49 DEGs and found 10 DEGs were associated with patients survival (P < 0.05). A risk model of 6-gene signature was constructed in TCGA training set and the model's predictive ability was confirmed with GEO validation set. Patients in the low-risk group survived longer than those in the high-risk group (P<0.05) in GEO validation sets. Functional study showed the two patient groups were associated with distinct immunity conditions and IC50. Conclusion: We constructed a prognostic model with 6 necroptosis-associated genes for HNSCC. The model has potential usage to guide treatment because prognosis and IC50 of most drugs are different between the two groups.